2020
DOI: 10.1136/bmjebm-2020-111506
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and COVID-19: review of evidence on risks and management considerations

Abstract: BackgroundRespiratory illnesses typically present increased risks to people with asthma (PWA). However, data on the risks of COVID-19 to PWA have presented contradictory findings, with implications for asthma management.ObjectiveTo assess the risks and management considerations of COVID-19 in people with asthma (PWA).MethodWe conducted a rapid literature review. We searched PubMed, medRxiv, LitCovid, TRIP, Google and Google Scholar for terms relating to asthma and COVID-19, and for systematic reviews related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 62 publications
1
62
0
4
Order By: Relevance
“…High temperature, myalgias, fatigue, and changes in taste/smell have been suggested as factors more likely to correlate to a COVID-19 infection rather than an asthma exacerbation, though these have not been validated. 14 In addition to education, there is a need for widely available COVID-19 testing with rapid turnaround of results, given that many of the early symptoms of COVID-19 and an asthma exacerbation can overlap.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…High temperature, myalgias, fatigue, and changes in taste/smell have been suggested as factors more likely to correlate to a COVID-19 infection rather than an asthma exacerbation, though these have not been validated. 14 In addition to education, there is a need for widely available COVID-19 testing with rapid turnaround of results, given that many of the early symptoms of COVID-19 and an asthma exacerbation can overlap.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 7 However, these assumptions have not been clearly demonstrated in numerous studies to date. 8 , 9 , 10 , 11 , 12 Early findings from Wuhan, China revealed that asthma was under-represented in COVID-19 infected patients, with the prevalence of asthma only at 0.9% among 548 patients with COVID-19, whereas the overall prevalence of asthma was 6.4% in the adult Wuhan population. 13 Similarly, COVID-19 infection was noted to be comparatively low in patients in the Severe Asthma Network in Italy, and asthma patients also had comparatively low mortality rates if infected.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Even though the prevalence of asthma among COVID-19 patients in Europe and the United States has been substantially higher, ranging from about 8% to 17%, asthma was not observed to be associated with an increased risk of adverse outcomes, such as hospitalization, intensive care unit (ICU) transfer, intubation, hospital readmissions, and mortality, in patients with COVID-19. 8 , 15 , 16 , 17 Several explanations for the surprisingly equivalent or favorable infection rates and outcomes of COVID-19 in asthma patients have been proposed including decreased epithelial angiotensin-converting enzyme 2 (ACE2) expression in asthma. 18 19 However, interestingly, a large cohort study from England identified asthma patients with recent oral corticosteroid use as being at increased risk for death due to COVID-19, while other studies found that asthma prolonged endotracheal intubation times.…”
Section: Introductionmentioning
confidence: 99%
“…No increased risk for COVID-19 related hospitalization nor ICU admission (32,33). Decreased asthma admissions reported in some centers (34,35).…”
Section: Asthmamentioning
confidence: 94%
“…At the beginning of the pandemic asthma was considered a risk factor for severe COVID-19. However, emerging data has not found asthma to increase risk of hospitalization nor ICU admission with COVID-19 infection (32,33). In a recent European Respiratory Society survey of 94 centers including 945 children with COVID-19, 49 (5%) children were asthmatic, most children had very mild symptoms and 20% presented with classic asthma exacerbations, potentially triggered…”
Section: Asthmamentioning
confidence: 99%